2014
DOI: 10.3109/13668250.2014.937326
|View full text |Cite
|
Sign up to set email alerts
|

Individual and organisational factors associated with the use of seclusion in disability services

Abstract: Background Seclusion is a restrictive intervention that results in some form of containment and social isolation of a person from others. Little is known about the relationships between individual and organisation factors and the use of seclusion in disability services. Method The reported use of seclusion in disability services in Victoria, Australia, was examined over a 3-year period, with a focus on the characteristics of those who were secluded (n = 146) and the characteristics of organisations that report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Positive behavioural support (PBS) is recommended by NICE (2015) as a way to ensure that people with intellectual disabilities have the best quality of life possible, as underpinned by their human rights. Evidence suggests that the use of PBS can reduce the need for seclusion and restraint (Allen et al, 2005; Webber et al, 2012), of which can be experienced as traumatic by the person and their professional carers (Bonner et al, 2002; Sequeira & Halstead, 2002). Previous research into PBS training has demonstrated positive impact on knowledge, emotional responding and attributions of staff (Macdonald & McGill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Positive behavioural support (PBS) is recommended by NICE (2015) as a way to ensure that people with intellectual disabilities have the best quality of life possible, as underpinned by their human rights. Evidence suggests that the use of PBS can reduce the need for seclusion and restraint (Allen et al, 2005; Webber et al, 2012), of which can be experienced as traumatic by the person and their professional carers (Bonner et al, 2002; Sequeira & Halstead, 2002). Previous research into PBS training has demonstrated positive impact on knowledge, emotional responding and attributions of staff (Macdonald & McGill, 2013).…”
Section: Introductionmentioning
confidence: 99%